Amphoteric Adsorbent Coating For Pharmaceutical Waste (Diclofenac Sodium) Removal - Abdul Taib, Muhammad Haziq (Universiti Sains Malaysia, 2021)
The removal of diclofenac sodium (DCF) using a novel amphoteric absorbent coating (AAC) has been presented by this thesis. The formulation of the adsorbent was through a formation of a layer on the surface of a cotton cloth through facile method application using acrylic polymer emulsion (APE), smectite-based clay powder, and cationic polyelectrolyte (EPIDMA). SEM and EDX analysis were conducted for the characterization of the adsorbent coating. The experiments were carried out to study the effect of EPIDMA dosage, concentration, contact time, temperature, and pH of DCF solution on the removal efficiency of the DCF. The optimized percentage removal of DCF is at 77.06% at DCF concentration of 50 mg/L, temperature of 30°C and pH of 3 for 5 hours. Adsorption isotherms were developed to study the adsorption mechanism of the adsorption. This study has shown that the aforementioned parameters influence the performance of the AAC for DCF removal. With high removal efficiency and reusability, AAC was found to be a promising adsorbent for DCF removal from pharmaceutical wastewater system.